SHOCK INDEX (SI) DAN MEAN ARTERIAL PRESSURE (MAP) SEBAGAI PREDIKTOR KEMATIAN PADA PASIEN SYOK HIPOVOLEMIK DI RSUD GUNUNG JATI CIREBON - Junaedi .; Janggan Sargowo; Tina Handayani Nasution (Jurnal Kesehatan Hesti Wira Sakti, 2016)
ABSTRAK Pendahuluan: Hipovolemik syok yang diakibatkan trauma maupun non trauma dapat menyebabkan kematian. Kematian disebabkan kehilangan sejumlah besar cairan tubuh atau darah yang terjadi pada kurang dari 24 jam atau 48 jam pertama sejak masuk Instalasi Gawat Darurat (IGD). Diperlukan pengenalan tanda-tanda pada pasien yang berisiko terhadap kejadian syok untuk meningkatkan angka harapan hidup. Penelitian ini bertujuan mengetahui pengaruh Shock Index (SI) yang dihasilkan dari perhitungan dari rasio denyut nadi (HR) dan tekanan darah sistolik (SBP) dan Mean Arterial Pressure dari perhitungan 1/3 SBP + 2/3 DBP (tekanan darah diastolik) yang bermanfaat memprediksi kematian pasien syok hipovolemik < 24 jam dan 48 jam pertama masuk ke IGD RSUD Gunung Jati Kota Cirebon, Jawa Barat. Metode: Penelitian ini menggunakan desain kohort retrospektif pada bulan Januari 2015 – April 2016, terdiri atas variabel independen SI dan MAP dan variabel dependen yaitu mortalitas yang dibagi < 24 jam dan 48 jam. Kelompok SI dan MAP dibagi masing-masing dalam dua kelompok, yaitu SI ≤ 0,9 dan SI > 0,9 dan MAP ≥ 60 dan MAP < 60. Hasil penelitian didapatkan sebanyak 29 data pasien, data SI dan MAP dicatat untuk dianalisa terhadap prediktor kematian < 24 jam dan 48 jam. Hasil dan Analisis: Analisis multivariat dengan regresi logistik menunjukkan MAP < 60 berpengaruh terhadap kematian pasien < 24 jam (Resiko Relatif (RR) 11,375, confidence interval (CI) 1,172-110,419, p = 0,036) dan memiliki nilai RR lebih tinggi dibandingkan dengan prediksi kematian 48 jam (RR 0,067 CI 0,007-0,653, p = 0,020). Area di bawah kurva (AUC) menunjukkan MAP 0,9 dan merupakan parameter yang cepat, akurat dan mudah digunakan. Kata kunci: syok hipovolemik, Shock Index, Mean Arterial Pressure, prediksi kematian. ABSTRACT Background: Hypovolemic shock resulting from traumatic injuries or nontraumatic continous to be the leading cause of death. Body of fluids loss or hemorrhagic deaths usually occur within the first 24 h or 48 h of admission to emergency department. Therefore, early identification of patients who are at risk for developing shock may improve survival. Objective the study was analyze whether the shock index (SI), given by the formula SI = heart rate/systolic blood pressure (HR/SBP), and Mean Arterial Pressure (MAP), given by the formula MAP = 1/3 SBP + 2/3 DBP (Diastolic Blood Pressure) are useful for predicting mortality at < 24 h and 48 h in hypovolemic shock adult patients admitted to the emergency department of Gunung Jati hospital at Cirebon City, West Java. Methods: A database of trauma patients admitted between January 2015 and April 2016 were retrospectively reviewed; the result according to the shock index and MAP were Independent variable determined, generating a dichotomous variable mortality was dependent variable with two groups: mortality at less than 24 h and mortality at 48 h, Both group SI and MAP divide into two groups for variable SI: (SI ≤ 0.9) and (SI > 0.9) and for variable MAP: (MAP ≥ 60) and (MAP < 60). Statistical analysis was performed. Results and Analysis: A total of 29 patients were analyzed, all had admission SI and admission MAP were noted to analyze with predictors of hostpital mortality by less than 24 h and 48 h. Multivariat regression analyses demonstrated that MAP < 60 correlate with predict hospital mortality less than 24 h (Risk Relative, RR 11,375, confidence interval (CI) 1,172-110,419, p = 0,036) and had higher RR of predict hospital mortality as compared to 48 h (RR 0,067 CI 0,007-0,653, p = 0,020) respectively. Study have used Receiver Operating Characteristic Curves to determine the accuracy of MAP in predicting hospital mortality by less than 24 h ranged from 0,555 – 0,939 (p = 0,043, AUC = 74,7%) that maintened higher sentivity (72,4%) specificity (68,9%) than 48 h (45% and 27,6%). Discussion and Summary: An initial MAP < 60 were strongest mortality predictor by less than 24 h greater than SI > 0,9 in hypovolemic shock adult patient in the emergency department and is also a quick, applicable and more accurate. Keyword: hypovolemic shock, Shock Index, Mean Arterial Pressure, mortality predictor